2016
DOI: 10.1364/optica.3.001483
|View full text |Cite
|
Sign up to set email alerts
|

Ultralinear heterogeneously integrated ring-assisted Mach–Zehnder interferometer modulator on silicon

Abstract: A linear modulator is indispensable for radio frequency photonics or analog photonic link applications where high dynamic range is required. There is also great interest to integrate the modulator with other photonic components, to create a photonic integrated circuit for these applications, with particular focus on silicon photonics integration in order to take advantage of complementary metal-oxide-semiconductor compatible foundries for high-volume, low-cost devices. However, all silicon modulators, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…The 500 nm thick silicon can achieve index matching between the silicon waveguide and the III-V epitaxial stack to provide a suitable Si/III-V hybrid mode in the gain section [34][35][36]. The use of a thick (500 nm) silicon layer has also been demonstrated to support high linearity heterogeneous silicon/III-V modulators [37] with high operating power [38], and high bandwidth photodetectors [9].…”
Section: Laser Design a Ultralow-loss Silicon Platformmentioning
confidence: 99%
“…The 500 nm thick silicon can achieve index matching between the silicon waveguide and the III-V epitaxial stack to provide a suitable Si/III-V hybrid mode in the gain section [34][35][36]. The use of a thick (500 nm) silicon layer has also been demonstrated to support high linearity heterogeneous silicon/III-V modulators [37] with high operating power [38], and high bandwidth photodetectors [9].…”
Section: Laser Design a Ultralow-loss Silicon Platformmentioning
confidence: 99%
“…As a result, they remain bulky (∼ 10 cm long), discrete, expensive, and require highpower electrical drivers [1,2]. Integrated silicon (Si) [4][5][6][7] and indium phosphide (InP) [8][9][10] photonics are promising solutions for scalability but come at the cost of compromised performance [4][5][6][7][8][9][10]. Here we demonstrate monolithically integrated LN electro-optic modulators that are orders of magnitudes smaller and more efficient than traditional bulk LN devices while preserving LN's excellent material properties.…”
mentioning
confidence: 99%
“…This paper addresses high optical power operation of the heterogeneously integrated III-V/SI MZI modulators through extensive device testing using a high power (1 Watt), polarization maintaining (PM) erbium doped fiber amplifier (EDFA). Additional previous work by the authors demonstrated III-V/Si RAMZI modulators with demonstrated SFDR at 10 GHz as high as 117 dB.Hz 2/3 [25], and suggested a further improvement in device linearization, using a novel Grating Assisted Michelson interferometer (GAMI) modulator [26].…”
Section: Introductionmentioning
confidence: 94%